Simultaneous RP-HPLC determination of sparfloxacin and dexamethasone in pharmaceutical formulations - Syed Naeem Razzaq; Muhammad Ashfaq; Irfana Mariam; Islam Ullah Khan; Syed Saleem Razzaq (Universidade de São Paulo, 2013)
The present study describes the development and subsequent validation of simple and accurate stability indicating RP-HPLC method for the determination of sparfloxacin and dexamethasone in pharmaceutical formulations in the presence of their stress-induced degradation products. Both the drugs and their stress-induced degradation products were separated within 10 minutes using C8 column and mixture of methanol and 0.02 M phosphate buffer pH 3.0 (60:40 v/v, respectively) as mobile phase at 270 nm using diode array detector. Regression analysis showed linearity in the range of 15-105 µg/mL for sparfloxacin and 5-35 µg/mL for dexamethasone. All the analytes were adequately resolved with acceptable tailing. Peak purity of the two drugs was also greater than 0.9999, showing no co-elution peaks. The developed method was applied for simultaneous determination of sparfloxacin and dexamethasone in pharmaceutical formulations for stability studies.